The globalization reader - Lechner, Frank J.; Boli, John, 1948- (Hoboken, NJ : Wiley-Blackwell, 2019)
'Since its initial publication, The Globalization Reader has been lauded for its comprehensive coverage of the issues surrounding globalization. Now in its sixth edition, the Reader has been thoroughly revised and updated and continues to review the most important global trends. Including readings by a variety of authors, the text offers a wide-ranging and authoritative introduction to the political, economic, cultural, and experiential aspects of globalization. The updated sixth edition presents the most accessible and comprehensive review of current debates and research. Contributions from scholars, activists, and organizations provide balanced viewpoints and expert coverage of the many aspects of globalization. The Globalization Reader offers readings on an exciting range of new topics as well as retaining key globalization topics such as the experience of globalization, economic and political globalization, the role of media and religion in cultural globalization, women's rights, environmentalism, global civil society, and the alternative globalization movement'--
Debating globalization -- Explaining globalization -- Experiencing globalization -- Globalization and the world economy -- Globalization and the nation-state -- Global governance -- Globalization, INGOs, and civil society -- Globalization and media -- Globalization and identity -- Global environmentalism -- Contesting globalization : alternatives and opposition.
Includes bibliographical references and index.
Buku bacaan asas siswazah Fakulti Ekonomi dan Pengurusan.
Keywords: International economic relations; International economic relations -- Social aspects; International economic integration; Globalization; Anti-globalization movement